Optical Topographic Imaging for Spinal Intraoperative 3-Dimensional Navigation in the Cervical Spine: Initial Preclinical and Clinical Feasibility. Issue 7 (August 2019) - Guha, Daipayan; Jakubovic, Raphael; Alotaibi, Naif M.; Deorajh, Ryan; Gupta, Shaurya; Fehlings, Michael G.; Mainprize, Todd G.; Yee, Albert; Yang, Victor X.D.
Abstract : Summary of Background Data: Computer-assisted 3-dimensional navigation may guide spinal instrumentation. Optical topographic imaging (OTI) is a novel navigation technique offering comparable accuracy and significantly faster registration workflow relative to current navigation systems. It has previously been validated in open posterior thoracolumbar exposures. Objective: To validate the utility and accuracy of OTI in the cervical spine. Study Design: This is a prospective preclinical cadaveric and clinical cohort study. Methods: Standard midline open posterior cervical exposures were performed, with segmental OTI registration at each vertebral level. In cadaveric testing, OTI navigation guidance was used to track a drill guide for cannulating screw tracts in the lateral mass at C1, pars at C2, lateral mass at C3–6, and pedicle at C7. In clinical testing, translaminar screws at C2 were also analyzed in addition. Planned navigation trajectories were compared with screw positions on postoperative computed tomographic imaging, and quantitative navigation accuracies, in the form of absolute translational and angular deviations, were computed. Results: In cadaveric testing (mean±SD) axial and sagittal translational navigation errors were (1.66±1.18 mm) and (2.08±2.21 mm), whereas axial and sagittal angular errors were (4.11±3.79 degrees) and (6.96±5.40 degrees), respectively. In clinical validation (mean±SD) axial and sagittal translational errors were (1.92±1.37 mm) and (1.27±0.97 mm), whereas axial and sagittal angular errors were (3.68±2.59 degrees) and (3.47±2.93 degrees), respectively. These results are comparable to those achieved with OTI in open thoracolumbar approaches, as well as using current spinal neuronavigation systems in similar applications. There was no radiographic facet, canal or foraminal violations, nor any neurovascular complications. Conclusions: OTI is a novel navigation technique allowing efficient initial and repeat registration. Accuracy even in the more mobile cervical spine is comparable to current spinal neuronavigation systems.